Functional Group Interconversion of Alkylidenemalononitriles to Primary Alcohols by a Cooperative Redox Operation - Emmetiere, Fabien; Grenning, Alexander J. (Synthesis, 2020)
Functional group interconversions are essential chemical processes enabling synthesis. In this report, we describe a strategy to convert alkylidenemalononitriles into primary alcohols in one step. The reaction relies on a choreographed redox process involving alkylidene reduction, malononitrile oxidation, and acylcyanide reduction where molecular oxygen and NaBH4 work cooperatively. The method was applied to a variety of carbon skeletons and was utilized to synthesize complex terpenoid architectures.
Keywords: Knoevenagel adducts; malononitriles; oxidative decyanation; redox processes; terpenoid synthesis